ANALISA NILAI CTDI DAN DLP PADA PEMERIKSAAN CT-SCAN ABDOMEN DI INSTALASI RADIOLOGI RSUD PROVINSI NTB - Mantofani, Nizar Azmi; Juliantari, Putu Eka; Mahendrayana, Made Adhi (Medical Imaging and Radiation Protection Research Journal, 2023)
One of the efforts to optimize radiation protection and safety in the implementation of diagnostic and interventional radiology procedures for patients is to apply the Diagnostic Reference Level (DRL) according to the type and object of examination carried out. The level of diagnostic guidance for medical exposure or DRL is highly recommended to be used as a guide for medical practitioners in optimizing protection in each type of diagnostic and interventional radiology examination and is used to prevent unnecessary radiation exposure in patients. Each Radiology Installation needs to conduct a routine evaluation of the dose value received by the patient and compare it with the latest Indonesian Diagnostic Reference Levels (IDRL) so that its implementation becomes effective. This study aims to evaluate the value of CTDI and DLP in the Adult Abdomen CT-Scan Examination at the NTB Provincial Hospital. This study uses descriptive quantitative research with a survey approach that aims to evaluate the value of CTDI and DLP in the Adult Abdomen CT-Scan examination at the NTB Provincial Hospital. This study was conducted by collecting data sourced from the Abdominal CT-Scan Examination. The facilities DRL value is calculated by using the quartile formula 3 (75 percentile) in Microsoft excel automatically, then compared with the latest IDRL value. The calculation of the quartile value of 3 (75 percentile) from CTDI and DLP received by patients at the adult Abdominal CT-Scan Examination at the NTB Provincial Hospital, obtained as many as 60 samples. Drl or quartile 3 (75 percentile) values obtained for CT-Scan Abdomen Contrast were 16.60mGy for CTDIvol and 1344.57mGy*cm for DLP. As for the Non-Contrast Abdominal CT-Scan of 15.15mGy for CTDIvol and 797.97mGy.cm for DLP. The value of 75 percentile of CTDI and DLP received by patients on the adult Abdominal CT-Scan Examination while at the Provincial Hospital is in accordance with the recommendations of BAPETEN / IDRL 2021.